Venous coupler use for free‐flap breast reconstructions: Specific analyses of TMG and DIEP flaps. Issue 4 (8th November 2014) - Bodin, Frédéric; Brunetti, Stefania; Dissaux, Caroline; Erik, A. Sauleau; Facca, Sybille; Bruant‐Rodier, Catherine; Liverneaux, Philippe
<x xml:space="preserve">Abstract</x> Purpose The purpose of this report was to present the results of comparisons of anastomotic data and flap complications in the use of venous coupler in breast reconstruction with the transverse musculocutaneous gracilis (TMG) flap and the deep inferior epigastric perforator (DIEP) flap. Methods Over a three‐year period, 95 patients suffering from breast cancer were treated with mastectomy and breast reconstruction using free flaps. We performed 121 mechanical venous anastomoses for 105 flap procedures (80 DIEP and 25 TMG). The coupler size, anastomotic duration, number of anastomoses and postoperative complications were assessed for the entire series. Results The coupling device was perfectly suitable for all end‐to‐end anastomoses between the vein(s) of the flap and the internal mammary vein(s). No venous thrombosis occurred. The mean anastomotic time did not significantly differ between the DIEP (330 seconds) and TMG flap procedures (352 seconds) (P = 0.069). Additionally, there were no differences in coupling time observed following a comparison of seven coupler sizes (P = 0.066). The mean coupler size used during the TMG flap procedure was smaller than that used with the DIEP (2.4 mm versus 2.8 mm) (P < 0.001). The mean size was also smaller when double venous anastomoses were required compared to single anastomosis (2.4 mm versus 2.9 mm) (P < 0.001). The double branching was more frequent with the TMG flap (28%) than with the DIEP flap (11%). Conclusions The coupler size used was smaller for the TMG procedure and when double venous anastomosis was performed. Additionally, anastomotic time was not affected by the flap type or coupler size used or by anastomosis number. © 2014 Wiley Periodicals, Inc. Microsurgery 35:295–299, 2015.